Climate claáification of Abies pinsapo Bois. forest in Southern Spain - Fernandez Cancio, A.=700 1 Navarro Cerrillo, R.M.; Fernandez Fernandez, R.
(Es, En)
ilus., 14 ref.
Keywords: ABIES PINSAPO; BOSQUES; VEGETACION; DISTRIBUCION GEOGRAFICA; CLIMATOLOGIA; ESPAÑA